Catholic interview : inter-departmental correspondence - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
010-0054-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From DR. H.B. MORGAN. Department: Social Insurance. To MISS F. McDONALD Date 12th November, 1936. SUBJECT. CATHOLIC INTERVIEW Yes, agreeable. So long as the report is regarded as a confidential one, and I am sure Mr. Middleton will treat it so. - He can certainly have it. 292/946/10/57